2021
DOI: 10.1177/10748407211031980
|View full text |Cite
|
Sign up to set email alerts
|

Digital or In-Person: The Relationship Between Mode of Interpersonal Communication During the COVID-19 Pandemic and Mental Health in Older Adults From 27 Countries

Abstract: Social distancing has limited the spread of the coronavirus (COVID-19), but also changed communication patterns. However, studies of how mental health in older adults relates to the usage of different modes of interpersonal communication are sparse. The aim of this study was to analyze how COVID-19-related changes in the frequencies of using different modes of communication (digital or in-person) have influenced mental health in older adults from 27 countries. Our study was based on part of Wave 8 of the SHARE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 36 publications
(52 reference statements)
0
41
0
Order By: Relevance
“…For example, Jaschinski and Allouch [54], citing their own and other studies, concluded that older research participants believed "that AAL [Ambient Assisted Living] technologies cannot and should not replace human assistance and human interaction, but should be used as a supplement to human care". The research from the COVID-19 pandemic supports the positive value of face-to-face communication with family and friends, as opposed to digital communication, particularly for older people who live alone [55,56]. However, the work of Strengers et al [8] suggests that, for those with these technologies in place, the COVID-19 crisis provided new adopters with the opportunity and perhaps motivation to learn how to use digital video communication tools and troubleshoot technical difficulties with online support.…”
Section: Discussionmentioning
confidence: 92%
“…For example, Jaschinski and Allouch [54], citing their own and other studies, concluded that older research participants believed "that AAL [Ambient Assisted Living] technologies cannot and should not replace human assistance and human interaction, but should be used as a supplement to human care". The research from the COVID-19 pandemic supports the positive value of face-to-face communication with family and friends, as opposed to digital communication, particularly for older people who live alone [55,56]. However, the work of Strengers et al [8] suggests that, for those with these technologies in place, the COVID-19 crisis provided new adopters with the opportunity and perhaps motivation to learn how to use digital video communication tools and troubleshoot technical difficulties with online support.…”
Section: Discussionmentioning
confidence: 92%
“…However, mediated communication is not the same as -or not socially and emotionally similar to -face-to-face communication. A study of how the altered frequency of using in-person and digital communication has influenced mental health in older adults during the pandemic (Skałacka & Pajestka, 2021) reveals that the in-person mode of interpersonal communication has benefited mental health more than the digital one. This may be explained by the fact that the use of digital communication technologies may remind elderly people of their feelings that ultimately they are alone during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…"When they hang up or turn off the communication application, they are left feeling alone again" (Skałacka & Pajestka, 2021, p. 279); this is especially so in communication with children as communication with a friend is based on different rules than communication with family members. The authors claim that "frequent digital communications can, paradoxically, increase the feeling of isolation and loneliness, because this form of communication can reduce the emotionality of existing relationships, making them shallower and forcing them into a more restrictive time frame" (Skałacka & Pajestka, 2021). Digital and/or telephone communication (support) might provide some emotional or psychological relief or some improvements by way of feeling more socially connected, but it can be lacking -due to the loss of certain cues that aid with communication such as touch, bodily movement, physical context, smell -social presence, warmth, impressions and thus a richer social experience.…”
Section: Discussionmentioning
confidence: 99%
“…Third, research conducted by Skałacka and Pajestka (2021). This type of research is descriptive research, using a quantitative approach method.…”
Section: Comparison Of Past Researchmentioning
confidence: 99%